1983
DOI: 10.1098/rstb.1983.0083
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation and multiplication of bacteria in host tissues

Abstract: The multiplication of bacteria in the largely undefined and changing environment of host tissues is an essential feature of any infection. Bacterial behaviour is determined both by genetic structures and also by the environment. Little is known about the effect that host factors may have on invading bacteria nor about the way in which alterations in bacterial properties aid proliferation in vivo . Recently our understanding of one feature of this environm ent and of the way in which pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

1985
1985
1995
1995

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 67 publications
(64 reference statements)
1
15
0
Order By: Relevance
“…Antigenic similarities between the receptor proteins of several E. coZi strains would help to explain why normal human sera from a range of sources contained antibodies to the 81 kDal protein of the test strains (Griffiths, 1983;Griffiths et al, 1985). The degree to which antibodies reacting with the iron-regulated outer membrane proteins, and specifically with the ferric enterobactin receptor, might be involved in host defence is unknown.…”
Section: H Chart a N D E Griffiths Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Antigenic similarities between the receptor proteins of several E. coZi strains would help to explain why normal human sera from a range of sources contained antibodies to the 81 kDal protein of the test strains (Griffiths, 1983;Griffiths et al, 1985). The degree to which antibodies reacting with the iron-regulated outer membrane proteins, and specifically with the ferric enterobactin receptor, might be involved in host defence is unknown.…”
Section: H Chart a N D E Griffiths Discussionmentioning
confidence: 99%
“…Recent results from this laboratory have shown that normal human adult sera contain naturally occurring IgG antibodies which react with the outer membrane proteins of E. coli (Griffiths, 1983;Griffiths et al, 1985). Interestingly, the major antigenic components recognized by these antibodies were the ompA proteins and the iron-regulated outer membrane proteins, including the enterobactin receptor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Iron is essential for the growth of most bacteria, but in vertebrates this element is found complexed to high-affinity iron-binding proteins and is unavailable for bacterial use (6,12,18,27). Pathogenic bacteria capable of causing disseminated infections have thus evolved specialized iron assimilation systems to overcome this first line of the host defense mechanisms.…”
mentioning
confidence: 99%
“…The subject is reviewed frequently (Griffiths, 1991 ;Litwin & Calderwood, 1993). The subject is reviewed frequently (Griffiths, 1991 ;Litwin & Calderwood, 1993).…”
Section: ( D ) Growth In Vivomentioning
confidence: 99%